Der siebenarmige Leuchter im Speculum humanae salvationis - Krenn, Margit (The Menorah and the seven-branched candelabrum, 2025)
Abstract: The Speculum humanae salvationisSpeculum humanae salvationis, written at the beginning of the 14th century, was the most widely used typological work of the late Middle Ages. Based on text-image combinations, the Speculum pairs events from the New Testament (‘antitypes’) with those from the Old Testament (‘types’). While these pairings serve as pictorial evidence of the fulfilment of the Old Testament, together they give an overall view of salvation history with a strong Marian emphasis. The seven-branched candelabrum in the Speculum is mentioned as an implement of the Temple of Jerusalem and presented as a ‘type’ for Mary. Together with the Ark of the Covenant and the presentation of Samuel it serves as a typological supplement to the presentation of Jesus in the Temple. The illustrations bear a striking resemblance in both shape and size to surviving monumental candelabra that served as church furnishings. This chapter first examines the originality of the Speculum author’s typological interpretation of the Menorah. It then considers whether liturgy may have inspired the author of the Speculum and its illustrators.